Job and worker flows in high adjustment cost settings - Varejão, José M. (2018)
This paper analyses the relationship between the size of adjustment costs and the intensity of labor market flows. I argue that high adjustment costs inhibit adjustment to temporary shocks, leaving adjustment to long-lived shocks unchanged. Worker turnover is also reduced because of the negative impact that adjustment costs have on churning.